1997
DOI: 10.1007/s004410050893
|View full text |Cite
|
Sign up to set email alerts
|

Effects of carbachol and catecholamines on ultrastructure and intracellular calcium-ion dynamics of acinar and myoepithelial cells of lacrimal glands

Abstract: The current study was carried out to investigate autonomic nervous control of secretory functions in the lacrimal gland. To distinguish the difference between the responses to cholinergic and adrenergic agonists in acinar and myoepithelial cells in the lacrimal gland of guinea pigs, the morphological and functional responses to the agonists were examined by electron microscopy and by digital-imaging analysis of the intracellular concentration of Ca2+ ([Ca2+]i) using fluorescent Ca2+-indicators (Fura-2/AM and I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 41 publications
3
31
0
Order By: Relevance
“…We suggest that the formation of actin-coated fusion intermediates is triggered by the initiation of compound fusion of individual SVs in the cytosol immediately upon CCH stimulation. Evidence for compound fusion of SVs has previously been obtained in lacrimal acini (Satoh et al, 1997) and related models (Cochilla et al, 2000;Ishihara et al, 2000;Campos-Toimil et al, 2002). This model is also supported by our findings of a significant increase in the individual SV diameter in CCH-stimulated acini.…”
Section: Discussionsupporting
confidence: 90%
“…We suggest that the formation of actin-coated fusion intermediates is triggered by the initiation of compound fusion of individual SVs in the cytosol immediately upon CCH stimulation. Evidence for compound fusion of SVs has previously been obtained in lacrimal acini (Satoh et al, 1997) and related models (Cochilla et al, 2000;Ishihara et al, 2000;Campos-Toimil et al, 2002). This model is also supported by our findings of a significant increase in the individual SV diameter in CCH-stimulated acini.…”
Section: Discussionsupporting
confidence: 90%
“…Parasympathetic cholinergic stimuli elicit an IP 3 -dependent [Ca 2+ ] i increase, while sympathetic adrenergic stimulation-induced [Ca 2+ ] i dynamics are IP 3 -independent (13, 28). We previously reported that NA and adrenaline induce an increase in [Ca 2+ ] i and exocytosis in acinar cells of lacrimal glands, while myoepithelial cells respond only to cholinergic stimuli (60). The results from our current study are consistent with these previous results.…”
Section: Expression Of Adrenoceptors In Rat Lacrimal Gland Acinar Cellssupporting
confidence: 93%
“…These cells have tapering processes that embrace the acini and may assist in salivary flow and provide structural support in the face of increased intraluminal pressure during salivary secretion (Sato et al, 1979). M3R receptors have also been localized to myoepithelial cells in rat lacrimal gland (Lemullois et al, Beroukas et al 1996), and stimulation of these receptors causes contraction of the myoepithelial cells (Satoh et al, 1997). The presence of M3R (present study) and aquaporin-1 (Gresz et al, 2001) on salivary gland myoepithelial cells also raises the interesting possibility that some of the effects of acetylcholine on secretion may be mediated indirectly through an action on the myoepithelial cells, rather than a direct effect of acetylcholine on the acinar cells.…”
Section: Distribution Of M3r In Human Salivary Glandmentioning
confidence: 99%